Pengaruh Penggunaan Aplikasi Quizizz Terhadap Minat Belajar Siswa Dalam Mata Pelajaran Matematika Kelas VIII SMP Negeri 4 Baubau - Ariesnita, Elsa Charisima Putri; Ugi, La Eru; Anwar, Anwar; Herlawan, Herlawan (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
The aim of this research is to find out the influence of using the Quizizz application on students’ learning interest on mathematics subject in class VIII at SMP Negeri 4 Baubau. This is a quantitative research by applying a correlational method, The population is all students in class VIII of SMP Negeri 4 Baubau with a total of 327 students spread across 11 classes. Meanwhile, the sample in this study was 58 students. The instrument used was a questionnaires regarding the use of the Quizizz application and students’ interest in leraning. The data were analyzed by using simple linear regression analysis. The results of this research can be concluded that, there is a significant influence of using the Quizizz application on students’ learning interest on mathematics subject in class VIII at SMP Negeri 4 Baubau.